BEHAVIOUR OF STOCK PRICES SINCE LIBERALIZATION: THE CASE OF FII IN INDIA - Mehta, Sonal (2008)
Stock market liberalization is a decision made by the Government of India to allow foreigners to purchase shares in the stock market of India. India is one of the biggest and fastest growing economies and has attracted more attention of the investors in the recent years. After liberalization in 1991, India has become one of the hotspots for global investment. Foreign Institutional Investors have given a boost to the economic growth of India and helped in financing it. The stock markets have grown in the past twenty years and the financial sector has become modern and well-disciplined.